(untitled) (Maharaja Surajmal Institute Law Journal, 2026)
The redesign of a modern, Indian-origin and fair legal order in the twenty first century requires a transformation of the criminal justice institution regarding its imperial, sanctioned, roots to victim-based paradigms. The statutes in Britain-era focused on preservation of dominion and maintenance of order by means of retribution and intimidation, neglecting any victim interests or involvement and redress. Centrality of states and offend ers leans toward continuity after independence, and implicates victims. With the requirements of Am Viksit Bharat 2047, it is necessary to shift the focus of decolonization to shift away the vengeful remains onto participa tory, empathetic victim primacy. This victim justice analysis is sensitive to the discourse of victim justice in India by exploring the shift of imperial punitive models to the participatory restorative architectures through Bharatiya Nyaya Sanhita (BNS), Bharatiya Nagarik Suraksha Sanhita (BNSS), and Bharatiya Sakshya Adhiniyam (BSA). It evaluates the effectiveness of reform in cutting the colonial ties and putting the victims at the center stage. Endless obstacles arise: restricted trial participation, inadequate redress and recovery, extended periods. Citing such international guidelines as the EU Victims Rights Directive, UK Victims Code and US Crime Victims Rights Act, the discussion puts the context of India in law development on the world stage and highlights the need to be culturally sensitive when adapting the law to fit the constitution. Doctrinal and cross-jurisdictional interrogation fosters a cohesive roadmap that strengthens victim rights by making formal and extended restorative usage and powerful redress structures. Finally, reformulation of punitive colonial law into victim-responsive and redressive laws is the key to indige nous just jurisprudence, which offers increased justice access, institutional credibility, and constitutional hopes of justice, honour, and equality on the road to Viksit Bharat 2047.